2004
DOI: 10.1128/aem.70.10.6113-6122.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Compositions and Metabolic Activities of Fecal Microbiotas in Young Adults and in Antibiotic-Treated and Non-Antibiotic-Treated Elderly Subjects

Abstract: The colonic microbiota mediates many cellular and molecular events in the host that are important to health. These processes can be affected in the elderly, because in some individuals, the composition and metabolic activities of the microbiota change with age. Detailed characterizations of the major groups of fecal bacteria in healthy young adults, in healthy elderly people, and in hospitalized elderly patients receiving antibiotics were made in this study, together with measurements of their metabolic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
283
10
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(326 citation statements)
references
References 50 publications
28
283
10
5
Order By: Relevance
“…For example, Tanaka et al (65) reported 59 and 98 % of Lactobacillus and Bifidobacteria strains, isolated from faeces are BSH positive. With age there are several changes to the gut microflora, including a decline in the number and species diversity of Lactobacillus and Bifidobacterium (8,66) . Therefore, it is possible that the age-related decline of these bacterial species reduces bile acid deconjugation, and in turn reduces the conversion of cholesterol to bile acid.…”
Section: Intrinsic Ageingmentioning
confidence: 99%
“…For example, Tanaka et al (65) reported 59 and 98 % of Lactobacillus and Bifidobacteria strains, isolated from faeces are BSH positive. With age there are several changes to the gut microflora, including a decline in the number and species diversity of Lactobacillus and Bifidobacterium (8,66) . Therefore, it is possible that the age-related decline of these bacterial species reduces bile acid deconjugation, and in turn reduces the conversion of cholesterol to bile acid.…”
Section: Intrinsic Ageingmentioning
confidence: 99%
“…Interest, as well as the number of studies, in the GI microbiota of elderly people has grown as life expectancy in the Western world has rapidly increased. The elderly have been reported to have relatively stable microbiota (93)(94)(95) . However, the microbiota of the elderly has been reported to be more diverse and to contain partly different core microbiota as compared with younger adults (93,94,96,97) .…”
Section: Agementioning
confidence: 99%
“…In addition, increasing evidence suggests that aging is associated with alterations in the gut microbiota (Bartosch et al 2004;Biagi et al 2010;Gavini et al 2001;Hopkins et al 2001;Hopkins and Macfarlane 2002;Mueller et al 2006;Woodmansey et al 2004). Moreover, elderly subjects living in hospitals and nursing homes are susceptible to increased pathogen challenges.…”
Section: Introductionmentioning
confidence: 99%